2019
DOI: 10.1186/s12986-019-0405-0
|View full text |Cite
|
Sign up to set email alerts
|

Subcutaneous fat mass is associated with genetic risk scores related to proinflammatory cytokine signaling and interact with physical activity in middle-aged obese adults

Abstract: Background and aimsSubcutaneous fat mass is negatively correlated with atherogenic risk factors, but its putative benefits remain controversial. We hypothesized that genetic variants that influence subcutaneous fat mass would modulate lipid and glucose metabolism and have interactions with lifestyles in Korean middle-aged adults with high visceral fat.Materials and methodsSubcutaneous fat mass was categorized by dividing the average of subscapular skin-fold thickness by BMI and its cutoff point was 1.2. Waist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Zhao et al ( 2018 ) also found that the IGF1R was selected in Meishan pigs, which may be related to the high fertility of this breed. SRC is related to food intake in mice (Yang et al, 2019 ), and ADCY2 is reported to affect human subcutaneous fat content, both of which are functionally relevant (Daily et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Zhao et al ( 2018 ) also found that the IGF1R was selected in Meishan pigs, which may be related to the high fertility of this breed. SRC is related to food intake in mice (Yang et al, 2019 ), and ADCY2 is reported to affect human subcutaneous fat content, both of which are functionally relevant (Daily et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, obesity-related genetic variants do not always equally influence obesity risk in different people because there are complex interactions between genetic and environmental factors, behavior, and the gut microbiota, influencing the actual obesity phenotypes. Recent studies have demonstrated that an individual genetic variant and lifestyle interactions influence the risk of obesity [13] and metabolic diseases [14,15] in Europeans and Asians [16]. For example, FTO genetic variants interact with the genetic and environmental factors that influence obesity risk [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Our study showed that the alteration of rs4072341 in adenylyl cyclase 2 ( ADCY2 ) gene also reduced the occurrence of gallstones. In addition, ( Daily et al, 2019 ) found that ADCY2 rs326149 affects subcutaneous fat, which is positively correlated with the amount of subcutaneous fat, resulting in a high level of serum high-density lipoprotein cholesterol level. Previous studies have shown that ADCY2 gene is expressed in the brain and encodes a membrane-binding enzyme for the synthesis of cyclic adenosine monophosphate (cAMP).…”
Section: Discussionmentioning
confidence: 99%